Application of design thinking as an innovation tool in project management in metallurgical sector (Research, Society and Development, 2021)
This work consists of demonstrating how Design Thinking as an innovation tool in project management contributes to the integration between people and the results of organizations that use this methodology. The research aims to assess the potential gain of using innovative methodologies such as Design Thinking in project management. The research methodology is exploratory-descriptive, qualitative in nature, using bibliographic research methods and taking credit for the experience of the author who works in the research area. To achieve the intended objectives, the study is based on questionnaires applied to professionals who use these tools. A workshop on Design Thinking and its application in projects was also considered, through consultation of the material of specialist professors from the MBA course in project management, which the author participated and successfully concluded. To obtain the data, a descriptive analysis of in-company training was performed in a company in the automotive sector, a multinational in the metallurgical sector, headquartered in Taubaté-SP. For this, a communication and project management training was applied, with the participation of 20 employees, using, in this meeting, active project management methodologies. The steps were: Brainstorming; Problem analysis; concept awareness and leveling; real case studies of success and failure; and practice with an agile innovation and methodology tool and activities based on the company's processes. Through a qualitative analysis, diagnostic interview with the company's leadership, it was identified that the management of client projects was lacking in innovative methods, as well as management indicators that could improve the expected results in the contracted projects. So the focus was to work on improving project management processes, introducing innovation tools such as Design Thinking, Canvas and methodologies based on the best project management practices of the PMI (Project Management Institute). It is concluded that active methodologies supported by a robust management system make it possible to generate innovations when used and disseminated as a management practice and with the involvement of people from different organizational levels and, mainly, to generate better results in the projects conducted by the organization.